Omega-3 fatty acids in schizophrenia. Part II: Clinical applications - Róg, Joanna; Stelmach, Ewa; Śpila, Bożena; Gajewski, Jacek; Juchnowicz, Dariusz; Korzeniowska, Aleksandra; Tomaka, Joanna; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2017)
Ω-3 unsaturated fatty acids are compounds belonging to the group of essential fatty acids (EFAs). The history of the discovery of EFAs dates back to the 1930s of the twentieth century, however, growing interest in ω-3 EFAs in the context of mental health has been observed since the year 2000. In view of their multidirectional action, these compounds are a promising form of adjunctive therapy of many illnesses, including psychiatric disorders. The present article aims to review the literature on the clinical applicability of ω-3 EFAs in treating schizophrenia. We present the results of preclinical studies in this area and the mechanisms of ω-3 EFAs action discussed by the authors. The randomized controlled trials (RCTs) evaluating the possibility of using ω-3 EFAs in schizophrenia are characterized in detail. The results of the tests are not clear, which may result from the methodological diversity of interventions made. Ω-3 EFAs seem to be a promising form of adjunctive therapy of schizophrenia. Further research is needed, which will allow for defining groups of patients in which intervention will bring the expected results.